2014
DOI: 10.1155/2014/230349
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Anti-Toxocaraand Anti-ToxoplasmaAntibodies in Patients with Schizophrenia Disorder

Abstract: Objective. The aim of the present study was to examine the relationship between Toxoplasma gondii and Toxocara spp. infections in patients with schizophrenia disorder. Method. A total of 100 patients with schizophrenia disorder and 95 healthy individuals participated in the study. Participants were tested for the presence of anti-T. gondii and anti-Toxocara spp. antibodies by ELISA and Western blotting. Data were analyzed using Chi-square test and Fisher9s exact test. Results. There were no differences in T. g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 43 publications
3
17
2
Order By: Relevance
“…In another study published in 2014, anti-Toxoplasma antibodies were detected in 34% of patients with schizophrenia and 47.39% of healthy controls. 14 The findings of the present study have shown inconsistency with other studies that have reported that seropositivity to T. gondii infection was significantly higher in patients with schizophrenia compared with that in healthy controls. The results of the study that was carried out by Çetinkaya et al 9 in the same hospital in Elazig in 2007 are noteworthy.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In another study published in 2014, anti-Toxoplasma antibodies were detected in 34% of patients with schizophrenia and 47.39% of healthy controls. 14 The findings of the present study have shown inconsistency with other studies that have reported that seropositivity to T. gondii infection was significantly higher in patients with schizophrenia compared with that in healthy controls. The results of the study that was carried out by Çetinkaya et al 9 in the same hospital in Elazig in 2007 are noteworthy.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, another study also reported that there was no statistically significant difference in the prevalence of toxoplasmosis among subtypes of schizophrenia. 14 Positive symptoms reflect an excess or distortion of the individual's normal functions, are not present in people in the normal population, and are mainly present during the acute stage of schizophrenia. Negative symptoms are characterized by the elimination or absence of normal behavior, and may appear months and years before the onset of positive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Reports from Iran illustrates different prevalence rates range from 12.8 to 80 % in different geographical regions and on different populations such as hemodialysis, diabetic and schizophrenia patients and also healthy general population (Assmar et al 1997;Bayani et al 2013;Borna et al 2013;Ebrahim Zadeh et al 2014;Ghorbani et al 1981;Khademvatan et al 2014;Shirbazou et al 2013). Ghorbani et al (1978) carried out one of the oldest studies in Iran on seroprevalence of toxoplasmosis among inhabitants of Caspian see basin.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of schizophrenia is estimated at 1% of the adult population. The onset of the disease is usually observed in late adolescence or early adulthood (11).…”
Section: Toxoplasma Gondii Infection In the Context Of The Risk Of Scmentioning
confidence: 99%
“…Khademvatan et al (11) show that in infected individuals the parasite influences the synthesis of neurotransmitters, particularly dopamine, which can lead to personality changes, psychotic symptoms, and in some cases neurological and psychiatric disorders. Behavioral changes and cognitive disorders have been observed in infected rodents.…”
Section: Relationship Between T Gondii and Modulation Of Neurotransmmentioning
confidence: 99%